Integrated Membrane Process for the Treatment and Reuse of Residual Table Olive Fermentation Brine and Anaerobically Digested Sludge Centrate - Carlos Carbonell-Alcaina; Jose Luis Soler-Cabezas; Amparo Bes-Piá; María Cinta Vincent-Vela; Jose Antonio Mendoza-Roca; Laura Pastor-Alcañiz; Silvia Álvarez-Blanco (Membranes, 2020)
Management of wastewater is a major challenge nowadays, due to increasing water demand, growing population and more stringent regulations on water quality. Wastewaters from food conservation are especially difficult to treat, since they have high salinity and high organic matter concentration. The aim of this work is the treatment of the effluent from a table olive fermentation process (FTOP) with the aim of reusing it once the organic matter is separated. The process proposed in this work consists of the following membrane-based technologies: Ultrafiltration (UF) (UP005, Microdyn Nadir), Forward Osmosis (FO) (Osmen2521, Hydration Technology Innovation) and Nanofiltration (NF) (NF245, Dow). The FO process was implemented to reduce the salinity entering the NF process, using the FTOP as draw solution and, at the same time, to concentrate the centrate produced in the sludge treatment of a municipal wastewater treatment plant with the aim of obtaining a stream enriched in nutrients. The UF step achieved the elimination of 50% of the chemical oxygen demand of the FTOP. The UF permeate was pumped to the FO system reducing the volume of the anaerobically digested sludge centrate (ADSC) by a factor of 3 in 6.5 h. Finally, the ultrafiltrated FTOP diluted by FO was subjected to NF. The transmembrane pressure needed in the NF stage was 40% lower than that required if the ultrafiltration permeate was directly nanofiltered. By means of the integrated process, the concentration of organic matter and phenolic compounds in the FTOP decreased by 97%. Therefore, the proposed process was able to obtain a treated brine that could be reused in other processes and simultaneously to concentrate a stream, such as the ADSC.